Pemberian Hidroterapi pada Pasien Hipertensi - Putri Amalyah Ambanaga; Sudarman; Brajakson Siokal; Ernasari (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Hypertension is a condition where the systolic blood pressure is more than or equal to 140 mmHg and the diastolic blood pressure is more than or equal to 90 mmHg after taking two or more measurements. This study aims to determine the effect of hydrotherapy on reducing blood pressure in hypertensive patients in the working area of the Bangkala Health Center, Makassar City. This study uses a quasi-experimental research design and the research design is one group pretest- posttest. This study used one intervention group. The samples used in this study were 16 people who had hypertension. The treatment group will be given hydrotherapy for 15 minutes with warm water temperature of 38-40oC every day for 7 days every morning. Data analysis used paired t-test. The statistical test results of the hydrotherapy treatment were effective in reducing blood pressure with a p value <0.05. Hydrotherapy treatment can reduce systolic blood pressure by 5.0 mmHg and reduce diastolic blood pressure by 5.5 mmHg. The results of the paired t-test of systolic and diastolic blood pressure pretest-posttest hydrotherapy p = 0.001 (p <0.05) means that both treatments have an effect on reducing blood pressure in hypertensive patients. The conclusion from this study is that hydrotherapy has an effect on reducing systolic and diastolic blood pressure in hypertensive patients